EVALUATION SYSTEM OF STATE ASSISTANCE FUNDS FOR EDUCATIONAL INSTITUTIONS IN ACEH: An analysis of the ministerial regulation and the theory of milk al-daulah - Maharani, Puteri Maizania; Nasrun, Mahdalena; Safira Mustaqilla (JURISTA: Jurnal Hukum dan Keadilan, 2025)
SMPN 1 Baitussalam is one of the recipients of BOS funds as referred to in Permendikbudristek No. 63 of 2023. However, the lack of transparency to the public and efficiency in its use raises issues that contradict Permendikbudristek No. 63/2023. This study examines the evaluation system for managing BOS funds in 2023 at SMPN 1 Baitussalam, Aceh Besar Regency, based on the concept of milk al-daulah, which emphasizes proper, transparent, and fair management. The method used is qualitative descriptive analysis with a formal juridical approach, data obtained through in-depth interviews, document studies, and field observations. The results of the survey indicate that SMPN 1 Baitussalam has effectively managed BOS funds by Permendikbud and the principles of milk al-daulah. However, the findings reveal that there are still instances where students are asked to contribute independently for competitions or school events, and some facilities, such as classroom chairs, are in unsuitable condition due to insufficient funds. Additionally, the BOS fund announcement board must be re-displayed to ensure public access. Therefore, this research recommends that the government increase the funding allocation to optimize school facilities.